The Analysis of Service Quality and Service Facilities on Public Satisfaction Through Public Trust at the Motor Vehicle Testing Management Unit, Cilincing, 2025 - Wahyu Wijayanto; Devi Marlita; Nursery Alfaridi S Nasution; Aang Gunawan; Zaenal Abidin (Dinasti Review, 2025)
Public service is a government activity within institutions or organizations aimed at meeting societal needs in accordance with regulations. Motor vehicle testing is the inspection of vehicle components, including trailers and semi-trailers, to ensure technical compliance and roadworthiness. According to Law of the Republic of Indonesia Number 25 of 2009 on Public Services, the state must fulfill citizens’ needs while guaranteeing their rights and obligations. Community decisions to reuse services are largely influenced by satisfaction with the services received, making service quality improvement a key element of bureaucratic reform.This study applies a quantitative approach using SEM-PLS. The Partial Least Square method is employed to test theories and identify relationships among latent variables. Findings show that public trust mediates the effect of service quality and facilities on public satisfaction.